2013
DOI: 10.1126/science.1241214
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota from Twins Discordant for Obesity Modulate Metabolism in Mice

Abstract: The role of specific gut microbes in shaping body composition remains unclear. We transplanted fecal microbiota from adult female twin pairs discordant for obesity into germ-free mice fed low-fat mouse chow, as well as diets representing different levels of saturated fat and fruit and vegetable consumption typical of the USA. Increased total body and fat mass, as well as obesity-associated metabolic phenotypes were transmissible with uncultured fecal communities, and with their corresponding fecal bacterial cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

97
2,384
5
51

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 3,192 publications
(2,618 citation statements)
references
References 75 publications
97
2,384
5
51
Order By: Relevance
“…Microbiota from obese and lean twins induced obesity‐associated or lean metabolic phenotypes in GF mice (Ridaura et al. 2013). Gut microbiota also affect the progression of inflammation (Honda and Littman 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Microbiota from obese and lean twins induced obesity‐associated or lean metabolic phenotypes in GF mice (Ridaura et al. 2013). Gut microbiota also affect the progression of inflammation (Honda and Littman 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mice previously colonized with an 'obese' microbiome lost weight when supplied with a 'lean microbiome' , but only if also fed a normal or low-fat diet. Diet alone had little effect 9 . Although this elegantly controlled experiment suggests great potential for the microbiome and related therapies to affect health, it also shows the microbiome's limits: the effect was dependent on other factors, in this case diet.…”
Section: How Much Do Experiments Reflect Reality?mentioning
confidence: 95%
“…"And that can be from a mouse that's obese because of a genetic mutation in leptin, or mice that are obese due to consuming a high-fat, highsugar diet. " Researchers have even shown that germ-free mice that receive gut microbes from an obese human donor gain more weight than those that receive them from a lean person 7 .…”
Section: Cause or Effect?mentioning
confidence: 99%